PERANAN PEMERINTAH DAN PARTISIPASI MASYARAKAT KELURAHAN PANRENG TERHADAP PENINGKATAN PEMBANGUNAN DI KECAMATAN BARANTI KABUPATEN SIDENRENG RAPPANG - Haeruddin Iskandar (PRAJA: Jurnal Ilmiah Pemerintahan, 2018)
The purpose of a study is to determine the role of the government to increase development in Sub Panreng District of Baranti Sidenreng Rappang To know the community participation in the increased development in Sub Panreng District of Baranti Sidenreng Rappang and To determine the role of government and community participation to increase development in Sub Panreng District of Baranti Sidenreng Rappang. The population of this study were 3100 people, while the sample is numbered 97 people. Data collection techniques used in this research is to use the technique (1) observation, (2) interviews, and (3) questionnaire. The collected data was then analyzed using frequency tables and percentages. The results of this study indicate that the role of governments in Sub indicator Panreng District of Baranti Sidenreng Rappang with a value of 74.28% instrumental category, indicator Village community participation Panreng District of Baranti Sidenreng Rappang with a value of 74.75% to the category of participation, and indicators of increased development in Panreng village Village District of Baranti Sidenreng Rappang value increased 80% category